The state of knowledge of young Italian medicolegal doctors on the law of provisions for informed consent and advance treatment directives: a multi-centric survey two years after the enactment of Law 219 of 2017. - Bolcato, Matteo; Feola, Alessandro; Sanavio, Matteo; Amadasi, Alberto; Crenna, Stefano; Landi, Gianluca; Tettamanti, Camilla (Acta Biomedica Atenei Parmensis, 2020)
Background. On 22 December 2017, Law number 219 was approved in Italy entitled “Provisions for informed consent and advance treatment directives”. We aim to examine the knowledge of these provisions of Italian medico legal fellows, and the ability of Italian university healthcare facilities to implement the principles of the new law.Methods. A survey was conducted by means of a questionnaire sent to members of a scientific society. The society had 357 members and represents more than 75% of the Italian doctors in training and 32 university healthcare facilities in Italy. 27 facilities and 45% of the society’s members participated in this enquiry.Results. The majority (68%) of those interviewed felt they had acquired an adequate knowledge of the Law but only 60% of them were able to indicate how for filing legally valid advance directives (60% vs. 40%) and only 37% knew how drafting a shared care plan. 89% of the pool felt that legal recognition of a patient’s self-determination was useful for enhancing the care relationship. The 74% of the facilities analyzed have organized training activities regarding the contents of the law but only 26% have updated their procedures on the practical implementation of the law and their informed consent forms. 60% of the facilities perform medico legal consultation activities and in 15% of the facilities, there has been resistance to the application of the law.Conclusion. Many of the facilities have performed training activities but lack effective implementation of the activities required. With increased knowledge and organization this could be overcome.